Behavior of Equity Risk Premium After a Catastrophic Event - Toivonen, Sami (fi=Turun yliopisto|en=University of Turku|, 2018)
The Study focuses on how the equity risk premium of selected financial institutions behaved after the global financial crisis and the Euro sovereign debt crisis. Equity risk premium is calculated as a result of historical and projected data by using free cash flow to equity formula. By solving the cost of equity and deducting country risk premium the result is a company specific equity risk premium. The risk premiums are then compared with stress test conducted by the European Banking Authority (EBA). The hypothesis is that the higher the equity risk premium the lower should the placement in the stress test be. I also found that the global financial crisis had less of an effect on equity risk premium than the Euro sovereign debt crisis. The hypothesis is rejected by statistical tests. In fact, the results show no correlation between equity risk premium and stress test placement. In efficient markets, investors should reward the more risk averse financial institutions with a lower risk premium. However, this study does not take a stand on the on-going debate of the efficiency of markets. Indeed, the efficient market hypothesis does allow short term predictability and anomalies to occur as a result of irrational investors. But as the mispricing of equity risk premium is persistent some behavioral finance concepts are discussed as possible reasons for the market behavior. The main concepts discussed are herd behavior and belief perseverance. As the markets were struck with uncertainty on effects of a bank failure of one institution, the uncertainty followed the whole European banking industry. Herd behavior is used as an explanation for the behavior of investors and as a reason for the spreading of the mispricing phenomenon. Belief perseverance, on the other hand, is used to find an explanation why the phenomenon persisted. In the analysis I found that some of the institutions bounced back better after the catastrophic event, yet there is no evidence of a correction in the data for equity risk premium and stress test placement. These findings should help to better understand how a global (Europe-wide) shock affects companies from different regions. Institutions based in more stable countries and regions are not rewarded for their more risk averse portfolios as they should be.